'Lonely night watchman's art': Circuits of exclusion, C-grade film and hybrid aesthetics of Miss Lovely. Issue 1 (1st April 2018) - Walia, Ramna
Since the 2000s, Bombay cinema has engaged in a nostalgic re-telling of its history through the industrial practice of film remakes and retro films. We see an industrially produced nostalgia for the past that commemorates Bombay cinema history through its stars, narrative strategies, art direction, costumes and remixes of old songs and dances. Such recovery of the past elicits questions on the 'invisible' histories of film practices, particularly the B- and C-circuit films, produced in Mumbai. The origin and definition of these films remain ambivalent – and despite accounting for a sizeable portion of annual film productions, these films remain underground as a 'bad object'. I focus on the slippery category of C-grade cinema and its exponential rise in Bombay. I then focus on Ashim Ahluwalia's cinephilic engagement with the industrial story of the C-circuit in Miss Lovely (2012) and argue that the film uses a hybrid formal structure of a multiplex fringe film that fuses documentary elements with long-form fictional narrative and embodies the contestations of industrial histories of the Bombay film cultures.